A apropriação de resultados de pesquisa e transferência de tecnologia em universidades federais brasileiras - Soares, Rosália Rodrigues Alves (2016)
This research aimed to verify the search results ownership model and existing technology transfer in Brazilian Federal Universities, pointing out the factors related to the amount of intellectual property rights records and the number of signed technology contracts. A study in a quantitative perspective was developed in two stages. At first, we carried out a documentary research in order to describe the Brazilian context of intellectual property. At the second time, a longitudinal survey was applied in Brazilian Federal Universities to describe this situation and point out the factors that influence this process. The data were tabulated and analyzed using frequency analysis and correspondence analysis. At the end of the analysis, there was a growth scenario both applications for protection as technology contracts. Were identified two bottlenecks in the process: the low involvement of universities in the technology transfer process and the discrepancy between required protection order and granted, urging the discussion if the university really is involved in the process of "capitalization of knowledge." In terms of the factors related to the greater amount of orders for protection, were identified institutional factors such as the actions of the university's innovation policy and the activities of the Center for Technological Innovation. However, no institutional factor showed strong relationship with the amount of developed technology contracts, so the growth of this sector could be associated with individual factors. In this way, this study presents some proposals for improvements, such as the emphasis on constant improvement of project negotiation, negotiation of intellectual property assets and commercialization of technology, and the qualification of professionals involved in the process.